1985
DOI: 10.1007/bf00464402
|View full text |Cite
|
Sign up to set email alerts
|

Failures in myringoplasty

Abstract: We analyzed those failures occurring in 417 myringoplasties. Forty-four drum re-perforations were found (10.6%), half of which occurred immediately after operation. Causes of these early failures included necrosis in the middle of the graft without infection (10 ears) and blunting of the anterior margins of the graft (7 ears). Infection was the most common cause of re-perforations in the later failures. Re-perforations also occurred more frequently when larger perforations were closed in contrast to repair of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…Other preoperative factors like dry or wet ear, site of perforation or the grafting technique did not affect the graft take rate. 15 In our series, postoperative follow up showed complete control of otorrhea in 49 patients in dry group and 48 patients in wet group. 2 in wet and 1 dry ears showed persistent ear discharge.…”
supporting
confidence: 50%
“…Other preoperative factors like dry or wet ear, site of perforation or the grafting technique did not affect the graft take rate. 15 In our series, postoperative follow up showed complete control of otorrhea in 49 patients in dry group and 48 patients in wet group. 2 in wet and 1 dry ears showed persistent ear discharge.…”
supporting
confidence: 50%
“…Some researchers are of the opinion that they are important variables in determining the post tympanoplasty hearing results [12][13][14]. On the other hand, some investigators have repeatedly emphasized that these variables do not in any way significantly influence the post-operative hearing results [4,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…This could probably be due to poorer vascular supply to a larger graft as a larger area of graft remains unsupported in space. 26 Aggarwal et al in their study observed higher success rates with smaller perforations (less than 50% of pars tensa). 27 Yoon et al in their study concluded that there were no significant relationships between surgical success rate and the status of the contralateral ear.…”
Section: Discussionmentioning
confidence: 82%
“…As a result, this might have affected the sound transmitting dynamics of the middle ear. 25 In a study conducted by Vartanien, 26 reperforations and graft failure were significantly more often in larger perforations sized >50% of drum area compared to smaller perforations (<50%). This could probably be due to poorer vascular supply to a larger graft as a larger area of graft remains unsupported in space.…”
Section: Discussionmentioning
confidence: 96%